Association of eating behavior and diet quality among students in Taruna Nusantara Senior High School, Indonesia - Triatmoko, Barkah; Chandra, Dian Novita; Khusun, Helda; Pramesthi, Indriya Laras; Sekartini, Rini (Indonesian Nutrition Association, 2025)
Background: Poor adolescent diet quality is influenced by family eating habits, media promoting unhealthy foods, and body image pressures, leading to disordered eating, neglect of health considerations, and obesity. Even in controlled environments like boarding schools. Objective: This study aims to assess association between eating behavior and dietary quality among students in Taruna Nusantara Senior High School (TN-SHS), Indonesia. Methods: A cross-sectional study with 200 subjects aged 15-18 was conducted in January 2024. Participants were purposively sampled from TN-SHS boarding school. Data was collected using the Dutch Eating Behavior Questionnaire (DEBQ) and Diet Quality Index International (DQI-I), along with sociodemographic information, nutritional status, and physical activity. Analysis was performed using SPSS 29, employing multiple linear regression to examine the relationship between eating behaviors and diet quality. Results: There was strong relationship between eating behavior and diet quality on different days, revealing that restrained eating correlates with better diet quality on average days (r=0.158, p=0.026), while external eating is linked to poorer diet quality. The association between eating behavior and diet quality on weekdays is weaker than on weekends. External eating consistently reduces diet quality across all periods (β=–1.380 to –1.854, p<0.01). Males exhibiting lower diet quality (β=–3.021 to –4.904, p≤0.002) and higher pocket money associated with improved diet quality, particularly on weekends (β=–3.633, p=0.021). Conclusion: The study findings highlight the importance of managing external eating behaviors such as emotional eating, social eating, mindless eating, and binge eating, and suggest avenues for targeted interventions to promote healthier dietary habits.